Inﬂuence of some environmental factors on growth of gray sea urchin (Strongylocentrotus intermedius) at the northwestern coast of the Japan Sea - M. O. Chalienko; V. N. Kulepanov; V. I. Matveev (Известия ТИНРО)
Habitat conditions, as qualitative and quantitative composition of aquatic vegetation and oceanographic factors, are compared for six populations of sea urchin Strongylocentrotus intermedius with different growth rate and mean size of individuals. The highest growth rate is observed in the areas between Cape Sosunov and Plitniak Bay, between Oprichnik Bay and Cape Grozny, and between Cape Lisuchenko and Kreiser Rock Island; all these areas are distinguished by high density and species diversity of macrophytes. On the contrary, the growth rate is the lowest at Cape Yuzhny where the vegetation is less abundant. All populations of slow-growing sea urchins inhabit the areas exposed to wave action that usually forms ﬂat rocky platforms: at Cape Yuzhny, at Cape Nadezhda, and between the Yezhovaya Bay and Cape Khitrovo. However, density of sea urchin populations in these areas is higher (on average from 9.8 to 20.8 ind./m2) than in the areas with relatively high growth rate (from 0.16 to 7.20 ind./m2). Any signifcant correlation between the water temperature and mean size of sea urchins, by ages, is not detected.